EKSPLORASI KARAKTER ENTREPRENEURIAL MARKETING PADA PEMILIK USAHA KECIL MENENGAH (UKM) - Damelina B. Tambunan (Business Management Journal, 2017)
This study aims to explore the entrepreneurial character owned by small and medium business owners in the city of Surabaya related in the field of marketing. The character is known by the term entrepreneurial marketing. Five informants were involved in this research, where they are the small and medium business owners (SMEs) in the field of food and beverages (F & B). Data collection's method is carried out by conducting in depth interviews with open-ended questions. data analyzed with four steps as follows: describe the (identification) of each individual character; perform grouping on the same character; analysis of each group and the present analysis and the final conclusion. This research was successfully concluded that each informant was successfully demonstrated that they have the entrepreneurial character of its business. The most dominant characters shown are interacting continuously with the targeted market. that means in the informant's experience in opening and managing his business provided by their ability to perform continuous interaction with the targeted market